TNT‐Induced Phagocytosis: Tunneling Nanotubes Mediate the Transfer of Pro‐Phagocytic Signals From Apoptotic to Viable Cells - Bittins, Margarethe (J Cell Physiol, 2017)
The exposure of phosphatidylserine (PS) on the surface membrane of apoptotic cells triggers the recruitment of phagocytic receptors and subsequently results in uptake by phagocytes. Here we describe how apoptotic cells can use intercellular membrane nanotubes to transfer exposed PS to neighboring viable cells, and thus deposit an “eat‐me” tag on the viable cells. Tunneling nanotubes (TNTs) connected UV‐treated apoptotic rat pheochromocytoma PC12 cells with neighboring untreated cells. These TNTs were composed of PS‐exposed plasma membrane and facilitated the transfer of the membrane from apoptotic to viable cells. Other pro‐phagocytic signals, such as oxidized phospholipids and calreticulin, were also transferred to viable cells. In addition, anti‐phagocytic signal CD47 presenting on the plasma membrane of viable cells was masked by the transferred PS‐membrane. Confocal imaging revealed an increase of phagocytosis of viable PC12 cells by murine RAW264.7 macrophages when the viable PC12 cells were cocultured with UV‐treated PC12 cells. Treatment with 50 nM cytochalasin D would abolish TNTs and correspondingly inhibit this phagocytosis of the viable cells. Our study indicates that exposed‐PS membrane is delivered from apoptotic to viable cells through TNTs. This transferred membrane may act as a pro‐phagocytic signal for macrophages to induce phagocytosis of viable cells in a situation where they are in the vicinity of apoptotic cells. J. Cell. Physiol. 232: 2271–2279, 2017. © 2016 The Authors. Journal of Cellular Physiology Published by Wiley Periodicals Inc.